FCR front-line therapy and quality of life in patients with chronic lymphocytic leukemia. Issue 2 (1st February 2017) - Kutsch, Nadine; Busch, Raymonde; Bahlo, Jasmin; Mayer, Jiri; Hensel, Manfred; Hopfinger, Georg; Hess, Georg; von Grünhagen, Ulrich; Wendtner, Clemens-Martin; Maria Fink, Anna; Fischer, Kirsten; Hallek, Michael; et al.
Abstract: The chemoimmunotherapy FCR (fludarabine and cyclophosphamide with rituximab) is the standard first-line treatment for physically fit chronic lymphocytic leukemia (CLL) patients. To assess the risks and benefits, we investigated health-related quality of life (HRQOL). 817 untreated CLL patients received either FC or FCR within the GCLLSG CLL8 trial. The European Organization for Research and Treatment of Cancer Quality of life Questionnaire C30 was sent to all patients at baseline, after 3, 6, and 12 months and then yearly as follow-up. A total of 769 (94%) of 817 patients completed at least one questionnaire. Comparing HRQOL of CLL patients with the general German population, CLL patients' health declined in most scales except for global health and pain. No major differences in HRQOL were found during treatment or follow-up between both treatment arms. Females were more likely to have treatment-related symptoms than males. Although FCR was associated with more side effects, this did not influence HRQOL. During follow-up after FCR only minor improvement of HRQOL compared with FC was assessed.